Physical Activity Using Social Media During the COVID-19 Pandemic: The Perceptions of Sports Science Students - López-Carril Samuel (Sciendo, 2021)
During the period of the COVID-19 lockdown, sports organizations and companies had to look for new ways to connect with their customers by offering physical activity (PA) alternatives to do at home. This study explores the perceptions of 175 undergraduate sports science students regarding their social media (SM) and PA patterns during the first Spanish COVID-19 lockdown period (March to May 2020). From their homes, the students completed an ad hoc online questionnaire. The data was analyzed using SPSS 23.0 software to perform descriptive and inferential analysis (t-test). The results show that the participants used SM during the COVID-19 lockdown to visualize or practice PA, perceiving SM platforms as channels through which to motivate themselves to perform PA, promote it or learn about new training disciplines. Significant gender differences were found with respect to the practice of PA using SM, with females showing higher scores than males. YouTube and Instagram were the most used SM platforms for viewing or practicing PA. In terms of practical implications, this study reinforces the role of SM in sports management for creating opportunities to connect with customers and offer innovative PA proposals in the challenging period brought on by COVID-19.